2022
DOI: 10.1101/2022.11.03.515024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimistic ants: Positive cognitive judgement bias but no emotional contagion in the antLasius niger

Abstract: Understanding the emotional states of animals is key for informing their ethical treatment, but very little attention has been directed towards the emotional lives of invertebrates. As emotions influence information processing, one way to assess emotional states is to look for an individual's cognitive bias, i.e., their tendency to make optimistic or pessimistic judgements. Here we developed a free-running judgment bias task for the ant Lasius niger, and applied the judgement bias to assess ants' reactions tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Previous studies indicated that fights alter biogenic amine and neurotransmitter levels in ants, which can lead to generally elevated aggression 29 . Also, emotion-like states can influence decisions after learning in Lasius niger ants 30 . Since this effect did not occur over multiple days in our experiment 2, it is likely that the biogenic amine levels normalise over such long times.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that fights alter biogenic amine and neurotransmitter levels in ants, which can lead to generally elevated aggression 29 . Also, emotion-like states can influence decisions after learning in Lasius niger ants 30 . Since this effect did not occur over multiple days in our experiment 2, it is likely that the biogenic amine levels normalise over such long times.…”
Section: Discussionmentioning
confidence: 99%